Role of surface pores on fouling of polyvinylidene fluoride membranes in submerged membrane bioreactors - Bilad, M.R. (Institute of Physics Publishing, 2017)
In this study, the roles of surface pores on membrane fouling was investigated using three membranes in two lab-scale membrane bioreactors. Characterization of the pristine membranes revealed that increasing polymer concentration decreases pore sizes and porosity. Critical flux was found to decrease with decreasing pore sizes. The finding was consistent for both MBRs. The results of the long-term filtration were in agreement with the flux-stepping test. The fouling layer was easily removed and only a few small particles remained as were observed with scanning electron microscopy. Surface pore sizes and porosity declined for all cleaned membranes, indicating permanent pore blocking, and the effect was higher for membranes with larger pore size. © Published under licence by IOP Publishing Ltd.